Interventions to reduce sickness absence among healthcare workers: a systematic review. Issue 2 (22nd March 2019) - Simmons, Laura; Jones, Arwel W.; Siriwardena, Niro; Bridle, Christopher
Abstract : Purpose: Sickness absence is a major concern for healthcare services and their employees with healthcare workers having higher sickness absence rates compared to the general population. The purpose of this paper is to systematically review randomised control trials (RCTs) that aimed to reduce sickness absence among healthcare workers. Design/methodology/approach: A systematic review was conducted that aimed to include RCTs with study participants who were employed in any part of the healthcare sector. This review included any type of intervention with the primary outcome measure being sickness absence. Findings: Seven studies were included in the review and consisted of one exercise-only intervention, three multicomponent intervention programmes, two influenza vaccination interventions and one process consultation. Three studies (exercise-only, one multicomponent intervention programme and one influenza vaccination intervention) were able to demonstrate a reduction in sickness absence compared to control. Research limitations/implications: Due to the lack of high-quality evidence, this review identified that there are currently no interventions that healthcare organisations are able to use to effectively reduce sickness absence among their employees. This review also highlights the importance of a standardised measure of sickness absence for healthcare staff, such as shifts. Originality/value: To the authors' knowledge, this is the first systematic review to synthesise such evidence among healthcare workers.